Impact of cellular morphology and three-tiered nuclear grade on progression of conventional renal cell carcinoma - Domonkos, Lilla; Yusenko, Maria; Kovacs, Gyula; Peterfi, Lehel (Journal of clinical pathology, 2024)
Aims and methods The aims of this study were to evaluate the prognostic impact of cytomorphology and three-tiered grading on tumour-free survival of patients with conventional renal cell carcinoma (cRCC). Formalin-fixed, paraffin-embedded samples from 710 patients were assessed and the results were evaluated according to the clinical data. - Results Kaplan-Meier regression model showed that 90.9% of patients with clear cell, and 50.9% with pure eosinophilic cRCC were free of metastasis during follow-up. The three-triered grading showed a good correlation with progression as 95.2% of patients with of G1 tumours, 66.1% with G2 tumours and only 25.3% with G3 tumours were tumour free (p<0.001). The grading was correlated with cytomorphology and coagulation necrosis. In multivariate analysis, tumour grade and stage were independent prognostic markers (p<0.001). - Conclusions The three-tiered grading predicts the progression of cRCC irrespectively of cytomorphology. However, the cytomorphology and necrosis show a good correlation with three-tiered grading in estimate disease progression.
Zuerst veröffentlicht: 19. Dezember 2023
Gesehen am 22.03.2024